Pelatihan Peningkatan Keterampilan Kader Posyandu Mulyasari, Tamansari, Kota Tasikmalaya - Sri Wahyuni Sundari; Winda Windiyani; Rissa Nuryuniarti; Melsa Sagita (Universitas Mathla'ul Anwar Banten, 2020)
TRAINING OF POSYANDU CADRE SKILLS OF MULYASARI, TAMAN SARI, TASIKMALAYA CITY. The implementation of posyandu activities is done by the cadre chosen and derived from the community. Given the role of a very large cadre in the management of Posyandu, it is necessary to increase the competency of cadres through training Posyandu Kader. The purpose of this community service is to improve cadre competence so that it can produce a reliable cadre in the development efforts of Posyandu, especially in the region. The training of Posyandu cadres is conducted through the pretest stage, training stage and post test. Public service activities conducted in July 2019 in the village of Mulyasari in the workplace Puskesmas in Tamansari City district. The number of Posyandu in Mulyasari village as many as 17 Posyandu, then took representatives of 2 cadres for each posyandu. The median understanding of cadres about the management of Posyadnu on Pretes is enough with as much as 61.8%; Good 23.5%, and less 14.7%, and after obtaining the average training cadre understanding increased to a good as much as 50%; Quite as much as 41.2% and less as much as 8.8%. Posyandu Kader Training is the right effort to improve the competency of Posyandu Kader. The cadres were enthusiastic to attend the training.